Utilization of a Wheat Sidestream for 5-Aminovalerate Production in Corynebacterium glutamicum - Burgardt, Arthur; Prell, Carina; Wendisch, Volker F. (Frontiers in Bioengineering and Biotechnology, 2021)
Production of plastics from petroleum-based raw materials extensively contributes to global pollution and CO2 emissions. Biotechnological production of functionalized monomers can reduce the environmental impact, in particular when using industrial sidestreams as feedstocks. Corynebacterium glutamicum, which is used in the million-ton-scale amino acid production, has been engineered for sustainable production of polyamide monomers. In this study, wheat sidestream concentrate (WSC) from industrial starch production was utilized for production of L-lysine-derived bifunctional monomers using metabolically engineered C. glutamicum strains. Growth of C. glutamicum on WSC was observed and could be improved by hydrolysis of WSC. By heterologous expression of the genes xylAXcBCg (xylA from Xanthomonas campestris) and araBADEc from E. coli, xylose and arabinose in WSC hydrolysate (WSCH), in addition to glucose, could be consumed and production of L-lysine increased. WSCH-based production of cadaverine and 5-aminovalerate (5AVA) was enabled. To this end, lysine decarboxylase gene ldcCEc from E. coli was expressed alone or for conversion to 5AVA cascaded either with putrescine transaminase and dehydrogenase genes patDAEc from E. coli or with putrescine oxidase gene puoRq from Rhodococcus qingshengii and patDEc. Deletion of the L-glutamate dehydrogenase encoding gene gdh reduced formation of L-glutamate as side-product for strains with either of the cascade. Since the former cascade (ldcCEc-patDAEc) yields L-glutamate, 5AVA production is coupled to growth by flux enforcement resulting in the highest 5AVA titer obtained with WSCH-based media.